Эксплуатация бурильных колонн геологоразведочного сортамента - Дудля, Н.А.; Викторов, Г.Н.; Кириченко, Г.Н. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2008)
In the article questions are considered the works of boring column related to the increase of efficiency in the geological survey boring drilling. Reasons of refusals of borings columns are analyses and the methods of completing by the selection of pair of screw-threads are offered, assembling with the necessary moment of screwing together. Methods and facilities are offered for the decline of wear of details of column.